Detection of Fasciola hepatica by indirect ELISA in sheep and goats from Boavita, Colombia - Cruz- Estupiñan, Sharon E. (2023)
The aim of this study was to determine the seroprevalence of Fasciola hepatica by indirect ELISA in sheep and goats from Boavita (Boyaca, Colombia). A descriptive cross-sectional study with simple random sampling was carried out. A total of 297 blood samples from sheep and 337 from goats of different breeds and age groups were collected. The sera were analyzed by the indirect ELISA technique with the commercial ELISA kit BIO K 211 - Monoscreen AbELISA F. hepatica. Additionally, an epidemiological survey was carried out. The seroprevalence of F. hepatica was 67.34% (200/297) in sheep and 59.94% (202/337) in goats. Likewise, seroprevalence was higher in males (sheep: 77.78%, 21/27; goats: 63.89%, 23/36), in sheep older than 3 years (83.33%, 50/60) and in goats less than 1 year of age. (69.77%, 60/86), as well as in Creole breed (sheep: 69.84%; goats: 61.79%). Sheep over 3 years of age were determined as a risk factor, while in goats the Creole breed variables and extensive grazing were identified as risk factors.